Prinsip Etos Kerja Untuk Perubahan - Karunia, Khaerunnisa; M, Misbahuddin; Ridwan, Saleh (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Work Ethic Is A Belief That A Person Has In Doing Something With The Determination To Work Hard And Give Their Best. People Who Have A Work Ethic Will Usually Be More Appreciated Because They Are Responsible For Every Job They Do. Besides That, Their Determination And Dedication To The Work They Do Makes Them Get More Value Than Others. This Can Increase The Chances Of Success In One's Career.Work In Islam Is Actually A Form Of Implementation Of Its Creation On Earth, As Caliph Fil Ardhi, Humans In Their Physical Form Are Ordered To Prosper The Earth And The Universe. Rasulullah Muhammad Saw Gave An Example That When He Was A Teenager He Was An Intelligent And Tenacious Worker. Thanks To This Hard Work, The Prophet's Trading Business Developed. Even When He Was Officially Appointed As An Apostle And Leader Of The Ummah, Prophet Muhammad's Work Spirit Did Not Weaken, World Affairs And Government, Economics And Even Building Fortifications For Military Strategy Were Still Being Worked On. Work Is An Obligatory Command In Islam In Line With The Obligatory Command To Provide A Living And Share With Others